Testicular cancer in men with undescended testis: Insights from the Thames Valley Testicular Cancer database. (July 2019) - Bryant, Richard J; Hobbs, Catherine; Richardson, Charlotte; Fox, Sebastian; Joseph, Johnson; Verrill, Clare; Woodcock, Victoria K; Sullivan, Mark E; Protheroe, Andrew S
Objective: Undescended testis (UDT) increases the risk of testicular cancer (TCa) development. Historical evidence suggests that malignant transformation of uncorrected UDT primarily results in seminomas, whereas mixed germ cell tumours predominate in corrected UDT; however, the risk of malignancy in the 'normal' contralateral testis is unclear. We investigated the contemporary Oxford TCa cohort to report the frequency of prior UDT and types of tumours developing in the prior UDT and normal contralateral testis. Patients and Methods: A 607 patient contemporary TCa cohort within the Thames Valley Testicular Cancer database. Results: Of men with new TCa, 8% had a history of UDT. Of men with TCa and prior UDT, 61% developed seminomas, whereas 56% of men with TCa without previous UDT developed this subtype. Among men with prior UDT, 77% developed tumours in the UDT, whilst 23% developed TCa in the contralateral normal testis. Conclusion: Seminoma was the most frequent malignancy following UDT, with a greater frequency than without prior UDT. Around one in four TCa patients with UDT developed contralateral tumours, emphasising the need for self-examination of both testes. Advice should be given to any patient with a history of UDT stressing the importance of ongoing self-examination of both testes. Level of evidence: Level 4.